Multisatellite MMS Analysis of Electron Holes in the Earth's Magnetotail: Origin, Properties, Velocity Gap, and Transverse Instability. Issue 9 (5th September 2020) - Lotekar, A.; Vasko, I. Y.; Mozer, F. S.; Hutchinson, I.; Artemyev, A. V.; Bale, S. D.; Bonnell, J. W.; Ergun, R.; Giles, B.; Khotyaintsev, Yu. V.; Lindqvist, P.‐A.; Russell, C. T.; et al.
Abstract: We present a statistical analysis of more than 2, 400 electrostatic solitary waves interpreted as electron holes (EH) measured aboard at least three Magnetospheric Multiscale (MMS) spacecraft in the Earth's magnetotail. The velocities of EHs are estimated using the multispacecraft interferometry. The EH velocities in the plasma rest frame are in the range from just a few km/s, which is much smaller than ion thermal velocity V T i, up to 20, 000 km/s, which is comparable to electron thermal velocity V T e . We argue that fast EHs with velocities larger than about 0.1 V T e are produced by bump‐on‐tail instabilities, while slow EHs with velocities below about 0.05 V T e can be produced by warm bistream and, probably, Buneman‐type instabilities. We show that typically fast and slow EHs do not coexist, indicating that the instabilities producing EHs of different types operate independently. We have identified a gap in the distribution of EH velocities between V T i and 2 V T i, which is considered to be the evidence for self‐acceleration (Zhou & Hutchinson,  2018) or ion Landau damping of EHs. Parallel spatial scales and amplitudes of EHs are typically between λ D and 10 λ D and between 10 −3 T e and 0.1 T e, respectively. We show that electrostatic potential amplitudes of EHs are below the threshold of the transverse instability and highly likely restricted by the nonlinear saturation criterion of electron streaming instabilities seeding electron hole formation: e Φ 0 ≲ m e ϖ 2 d | | 2, where ϖ  = min( γ,  1.5 ω c e ), where γ is the increment of instabilities seeding EH formation, while ω c e is electron cyclotron frequency. The implications of the presented results are discussed. Key Points: Slow and fast electron holes are present in the Earth's magnetotail and produced by instabilities operating independently The velocity gap in distribution of electron hole velocities is the evidence for self‐acceleration or ion Landau damping of electron holes The transverse instability and nonlinear saturation criterion of electron streaming instabilities can control electron hole amplitudes